Automatic Machine Control System Using Arduino Microcontroller - Harfizar, Harfizar; Wardoyo, Rizky Adytya; Atmojo, Tito Tri; Supriyono, Ignatius Agus (UNIVERSITAS RAHARJA, 2024)
Filling the tank with water uses a water machine to suck and put water into it. Water tanks are used to store clean water for household needs, especially from wells. This system requires manual supervision. The machine must be turned on if the tank is empty and turned off if it is full. If you forget to turn off the machine, the water will overflow and cause waste of water and electricity. Technological developments encourage the use of microcontrollers to overcome this problem. A microcontroller is a chip that processes digital data with a special language. Microcontrollers can be used as electronic controllers and to store programs. By using this technology, the problem of wasting water can be reduced. An automatic control system with an Arduino microcontroller can turn the water machine on and off automatically when the tank is empty and full. It is hoped that this system can help humans use water and electricity effectively and efficiently.